The Corrosion Behavior of N80 Steel in Multiple Thermal Fluid Environment Containing O2 and CO2 - Lin, Xueqiang; Luo, Xiaokang; Liu, Wei; Chen, Yufan; Pang, Bo; Guo, Yi; He, Qingkun (Frontiers in Materials, 2021)
The corrosion behavior of N80 steel in Multiple thermal fluid environment containing O2 and CO2 is analyzed by Scanning Electron Microscopy (SEM), Energy-dispersive Spectrometry (EDS), X-ray Diffraction (XRD) and electrochemical techniques. The results show that the corrosion products formed on N80 steel is a double-layer film structure. The outer corrosion products are loose and porous, providing less protection. The inner corrosion products are mainly FeCO3 crystals and a small amount of Fe2O3 and FeOOH, and the formation of Fe2O3 destroys the integrity of the inner layer, resulting in localized corrosion. During the development of pitting, Cl- is only enriched at the bottom of the pits, which is the main cause of pitting corrosion and eventually leads to the formation of dendritic localized corrosion. The difference between inner and outer layer potential, the O2 concentration and the decrease of pH in the pits combined to increase the corrosion process.